1995
DOI: 10.1300/j045v07n02_01
|View full text |Cite
|
Sign up to set email alerts
|

Accessing an Understudied Population in Behavioral HIV/AIDS Research:

Abstract: Most HIV/AIDS behavior research involving African American women has focused on traditional high risk populations, such as those in drug treatment centers, STD clinics, and hospitals. Few studies have examined the health needs and behaviors of African American women in the general population (i.e., working mothers and homemakers). The Parent Health Project examined beliefs and concepts of illness, including AIDS, of low income African American mothers of young children. We used a variety of methods of communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…Although the prevalence of women with incarcerated partners has not been systematically documented, 7% of the 4,349 female respondents to the National Sexual Health Survey (a national household probability sample) reported having a male primary partner who had been in prison or jail (Catania, 2000). In addition, a general population study of urban African American women found that 22% had a current sexual partner who had been incarcerated (Battle, Cummings, Barker, & Krasnovsky, 1995). The latter figure is consistent with the fact that African American men have been disproportionately affected by incarceration: 832,000 of the nation's 1.9 million male inmates are African American, and 13% of Black men in their 20s are behind bars compared to 3.7% of Hispanics and 1.6% of Whites (Harrison & Karberg, 2004).…”
mentioning
confidence: 70%
“…Although the prevalence of women with incarcerated partners has not been systematically documented, 7% of the 4,349 female respondents to the National Sexual Health Survey (a national household probability sample) reported having a male primary partner who had been in prison or jail (Catania, 2000). In addition, a general population study of urban African American women found that 22% had a current sexual partner who had been incarcerated (Battle, Cummings, Barker, & Krasnovsky, 1995). The latter figure is consistent with the fact that African American men have been disproportionately affected by incarceration: 832,000 of the nation's 1.9 million male inmates are African American, and 13% of Black men in their 20s are behind bars compared to 3.7% of Hispanics and 1.6% of Whites (Harrison & Karberg, 2004).…”
mentioning
confidence: 70%
“…Although the prevalence of women with incarcerated partners has not been systematically documented, 7 percent of the 4,349 female respondents in the National Sexual Health Survey (a national household probability sample) reported having a male primary partner who had been in prison or jail. In addition, a study of low-income urban African American mothers found that 22 percent had a current sexual partner who had been incarcerated (Battle et al 1996). …”
Section: Families Of the Incarcerated And The Consequences They Bearmentioning
confidence: 99%
“…Furthermore, the multi-site evaluation of the Serious and Violent Offender Reentry Initiative reported that 75% of incarcerated fathers were either married or in an intimate relationship (Lattimore, Visher et al, 2008), and a study of low-income African-American women found that 22% had a current male partner who previously had been incarcerated (Battle, 1995). These findings indicate that at any given time, millions of women are either separated from a partner who is behind bars or are reuniting with a partner who is returning home from a correctional facility.…”
Section: Introductionmentioning
confidence: 99%